A retrospective audit of the clinical value of routine chest radiographs in the first 24 hours after cardiac surgery using medical records - Nyoka-Mokgalong, Simangele Cecilia (Department of Anaesthesia, 2016)
Routine postoperative chest radiography after cardiac surgery is a common practice, although studies, both prospective and retrospective, conducted in their majority outside Africa, have shown that these chest radiographs are of low clinical value, mainly due to limited impact on patient management. Following cardiac surgery and admission to ICU, chest radiographs are obtained in order to ensure proper position of all invasive devices such as endotracheal tubes, invasive catheters as well as nasograstric tubes, and to exclude possibility of a pneumothorax, atelectasis, infiltrates, and other potential respiratory complications associated with ventilatory support. Following cardiac surgery, there are other elements that require assessment: mediastinum (for widening due to bleeding), pleural space (for presence of fluid or air) and cardiovascular system (for presence of signs of failure). Specific to cardiac surgery is the post-operative pulmonary dysfunction (PPD), where systemic inflammatory response due to cardiopulmonary bypass is the main culprit [Milot J et al, 2001] - leading to acute lung injury. Over and above the usual cardiovascular diseases that require surgical intervention, in Sub-Saharan Africa, inflammatory and infective conditions such as pulmonary tuberculosis, pulmonary hydatid disease, and pulmonary complications of HIV infection, are very prevalent. These pre-existing lung pathologies predispose patients to postoperative pulmonary complications after cardiac surgery. This audit investigates the role and importance of bedside chest X-rays in post operative care of cardiac surgery patients that come from a population group where lung pathology is quite prevalent.